A Key Role for Subiculum-Fornix Connectivity in Recollection in Older Age - Hartopp, Naomi; Wright, Paul; Ray, Nicola J.; Evans, Tavia E.; Metzler-Baddeley, Claudia; Aggleton, John P.; O’Sullivan, Michael J. (Frontiers in Systems Neuroscience, 2019)
Individual differences in memory during ageing are associated with the microstructure of the fornix, a bidirectional tract connecting the hippocampus with the diencephalon, basal forebrain and cortex. To investigate the origin of alterations in fornix microstructure, measurement of hippocampal subfield volumes was combined with diffusion MRI and cognitive evaluation in a new sample of 31 healthy human participants aged 50-89 years. The fornix, uncinate and parahippocampal cingulum were reconstructed using diffusion MRI tractography. Episodic memory was assessed with free and cued verbal recall, visual recognition and paired associate learning tests. Recall performance was associated with fornix microstructure and hippocampal subfield volumes. Subiculum and CA1 volumes remained positively associated with fornix microstructure when controlling for other volumes. Subiculum volume was also associated with fornix microstructure independent of age. Regression analyses showed that subiculum-fornix associations explained more variation in recall than that of CA1-fornix associations. In a multivariable regression model, age and subiculum volume were independent predictors of free recall whilst fornix microstructure and CA1 volume were not. These results suggest that age-related changes in a network that includes the subiculum and fornix are important in cognitive change in healthy ageing. These results match anatomical predictions concerning the importance of hippocampal – diencephalic projections for memory.